"It Lives!": Frankenstein, Presumption, and the Staging of Romantic Science. Issue 2 (4th March 2017) - Robbins, John
ABSTRACT: This article examines the relationship between Frankenstein and its stage adaptation Presumption in light of contemporary scientific developments. It argues that both the play and its source text function to shape and regulate public skepticism about potentially threatening new advances in the life sciences, ones that, like the Creature, threatened to overwhelm their creators. It closes by situating both Frankenstein and Presumption within a broader movement during the Romantic period toward the incorporation of science into everyday public life, one in which the theater played a crucial role.